Band edge modulated conjugated polymers for oxidation prevention - Mahale, Rajashree Y.; Arulkashmir, Arulraj; Dutta, Kingshuk; Krishnamoorthy, Kothandam (Physical Chemistry Chemical Physics, 2012)
The impact of electron transfer (ET) from a series of band edge modulated polymers to atmospheric oxygen is examined in connection with substrate oxidation prevention. Polymers with the highest occupied molecular orbital (HOMO) energy level below and above the oxygen energy level were tested and the former showed better efficiency. Furthermore, the oxidation prevention efficiency of a polymer with lower HOMO increased by two orders of magnitude, when the pores on the film were filled with spherical molecules, [6,6]-phenyl-C61-butyric acid methyl ester. We found that the polymer surface hydrophobicity has little or no influence on oxidation prevention. It is interesting to note that a polymer with a hole mobility of 8 x 10(-10) cm(2) V-1 s(-1) showed a two-fold increase in oxidation prevention efficiency compared to a polymer with a hole mobility of 6 x 10(-5) cm(2) V-1 s(-1). Over all, from the concerted approach, we conclude that a polymer devoid of pores with the HOMO energy level below oxygen and low charge carrier mobility is a suitable candidate for prevention of substrate oxidation/corrosion.

Reversible assembly and disassembly of micelles by a polymer that switches betweenhydrophilic and hydrophobic wettings - Dutta, Kingshuk; Mahale, Rajashree Y.; Arulkashmir, Arulraj; Krishnamoorthy, Kothandam (Langmuir, 2012)
Supramolecular complexes involving nanoscopic amphiphilic assemblies (AAs) and polyelectrolytes have been used to prepare a variety of materials, wherein the dynamic AAs retain the structural features, but the polyelectrolytes undergo conformational changes. Here we show that a charge bearing rigid conjugated polymer can alter the structural features and disassemble AAs. We also demonstrate reversible assembly and disassembly of AAs by controlling the number of charges on the rigid polymer. During the disassembly, the guest molecules sequestered in the AAs are released. The rate of release has been modulated by changing the morphology of the charge bearing polymer. Concomitant to the AAs disassembly, the polymer surface becomes hydrophobic due to the binding of the amphiphiles on the charges of the polymer backbone. By controlling the charges on the polymer, the surface wettability was varied gradually from hydrophilic to hydrophobic.